2004
DOI: 10.1136/tc.2003.005488
|View full text |Cite
|
Sign up to set email alerts
|

Designated “no smoking” areas provide from partial to no protection from environmental tobacco smoke

Abstract: Objective:To determine the efficacy of designated “no smoking” areas in the hospitality industry as a means of providing protection from environmental tobacco smoke (ETS), and whether certain design features assist in achieving this end.Methodology:In the greater metropolitan region of Sydney, a representative group of 17 social and gaming clubs, licensed to serve alcoholic beverages and in which, apart from designated areas, smoking occurs, agreed to participate. In each establishment, simultaneous single mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 16 publications
5
33
0
3
Order By: Relevance
“…The increased levels of PM 2.5 measured in nonsmoking rooms of venues with separate smoking room are also consistent with previous studies demonstrating that in venues with designated smoking rooms, tobacco smoke penetrates into adjoining rooms (Cains, Cannata, Poulos, Ferson, & Stewart, 2004;Huss et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…The increased levels of PM 2.5 measured in nonsmoking rooms of venues with separate smoking room are also consistent with previous studies demonstrating that in venues with designated smoking rooms, tobacco smoke penetrates into adjoining rooms (Cains, Cannata, Poulos, Ferson, & Stewart, 2004;Huss et al, 2010).…”
Section: Discussionsupporting
confidence: 79%
“…A study in Swiss restaurants, cafes and bars showed that PM2.5 levels in non-smoking areas were considerably increased if smoking was allowed anywhere in the same location, and were more than double those in completely smoke-free areas 21. Another study in clubs of Australia found that spatially separated non-smoking rooms had only marginally reduced PM10 and CO 2 22. In addition, several longitudinal studies indicated that a partial smoking ban provides no protection to SHS exposure in hospitals and workplaces 7 23 24.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Children living in multiunit housing have more exposure to secondhand smoke than those living in free-standing homes. 5 Furthermore, people living in multiunit housing have little control over their exposure to secondhand smoke since much of the air entering their apartments originates somewhere else in the building.…”
mentioning
confidence: 99%